Inovasi Pelayanan Publik di China: Suatu Pembelajaran bagi Pemerintah dalam Peningkatan Layanan Publik di Indonesia - Purwadi Purwadi; Anugerah Yuka Asmara; Wahid Nashihuddin; Aditya Wisnu Pradana; Anggini Dinaseviani; Ria Jayanthi (Jurnal Administrasi dan Kebijakan Publik, 2020)
Innovation is becoming a warming issue to be often discussed by many actors like academician, politician, and business sectors at global world recently. Innovation is basically a better change of an organization, it is firstly applied in private sector. Development of current literature in public administration science, innovation emerges as a conceptual discourse stuff that is then sounded into public sector. Innovation practice in private sector is different to public sector. Innovation practice in public sector, particularly in public services is one of interesting things to be discussed in this study because China is one of economics superpower in the world that is able to innovate at midst totally strong political control from central government. Issue of public service innovation is critical issue which is linear with economic growth in China. This study is a research using qualitative-descriptive method with the source derived from secondary data, and this study is called as a desk research. This research finding is that innovation practices at public service which is successfully conducted by Government of China can be adopted by Government of Indonesia by adjusting key points for implementing innovation of public services in Indonesia. It is important that Government of Indonesia must seek an alternative way to find an appropriate model to implement best practices of public service innovation adopted from China.